EVALUASI SARANA DAN PRASARANA DI PERPUSTAKAAN MADRASAH ALIYAH NEGERI 2 PONTIANAK - Anisah Alrasyiidah; Amriani Amir (Universitas Tanjungpura, 2021)
AbstractThis research is based on the lack of facilities that have an impact of facilities and infrastructure of ered to students to visit the Library Madrasah Aliyah Negeri Pontianak, and library services and management. The purpose of this reserch to explain the existing facilities and infrastructure in the library and review how to use it. The reserch is using qualitative, methods, adn descriptive forms, data collection techniques are done through observation of documentation and interviews conducted with 3 (three) informants. The results of this reserch explain that the facilities and infrastructure in the library are stiel lacking for buildings/rooms, equipment and supplies. Buildings/rooms are only about the size of class room around 8mx7m, its indaquate because its not balanced with all of students in Madrasah Aliyah Negeri 2 Pontianak. Library equipment are incomplete such as the lack of book shelves so many books are not neatly arranged and there are no tables and chairs reading to readers the need for additional equipment and supplies to have comfort, needs, satisfaction of visitor who come to visit the library.Keywords: Evaluation, Facilities and Infrastructure, School Library